2016
DOI: 10.1016/j.pscychresns.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of brain activation patterns during executive function tasks in hoarding disorder and non-hoarding OCD

Abstract: We examined differences in regional brain activation during tests of executive function in individuals with Hoarding Disorder (HD), Obsessive Compulsive Disorder (OCD), and healthy controls (HC) using functional magnetic resonance imaging (fMRI). Participants completed computerized versions of the Stroop and Go/No-Go task. We found that during the conflict monitoring and response inhibition condition in the Go/No-Go task, individuals with HD had significantly greater activity than controls in the anterior cing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 70 publications
(83 reference statements)
3
49
1
Order By: Relevance
“…Nine datasets were available to be included as whole-brain t-maps in the current meta-analysis (4,18,19,24,26,35,37,41,51). Peak coordinate data from a whole-brain analysis were available for a tenth dataset for the between-group errors contrast (40).…”
Section: Included Studies and Characteristicsmentioning
confidence: 99%
“…Nine datasets were available to be included as whole-brain t-maps in the current meta-analysis (4,18,19,24,26,35,37,41,51). Peak coordinate data from a whole-brain analysis were available for a tenth dataset for the between-group errors contrast (40).…”
Section: Included Studies and Characteristicsmentioning
confidence: 99%
“…These findings, however, are inconsistent, and most studies focused on compulsive hoarding as a subtype of OCD. Only one fMRI study reveals that HD patients diagnosed with DSM‐5 criteria exhibited significantly greater activity than controls in the anterior cingulate cortex and right dorsolateral prefrontal cortex during conflict‐monitoring and response‐inhibition conditions in the Go/No‐Go task . As far as we know, no studies have examined the structural changes relevant to hoarding by applying the diagnostic criteria of HD in the DSM‐5.…”
Section: Neuroimaging Studies Of Hoarding Symptoms and Hdmentioning
confidence: 99%
“…First, hoarding symptoms in the context of OCD may be neurologically different from HD. Several neuroimaging and neurophysiological studies have shown that individuals with OCD with hoarding show different patterns of activity from individuals with OCD without hoarding (Hough et al, ; Mataix‐Cols et al, ; Mathews, Perez, Delucchi, & Mathalon, ; Saxena et al, ).…”
Section: Discussionmentioning
confidence: 99%